Nativism traditions of the first wave of Rus- sian emigration in the works by V. N. Krupin - Kabylkova, Aliaksandra A. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the preserving of nativism traditions of Russian-language literature abroad during the first wave of emigration in the creative work of the modern writer V. N. Krupin. There were compared the works of some writers: V. N. Krupin and I. S. Shmelev («Religious procession» and «Pilgrimage»), V. N. Krupin and B. K. Zaytsev («Sergiy Radonezhskiy» and «The Reverend Sergiy Radonezhskiy», «The Holy Mt. Athos» and «The Holy Earth. There, where His foots step»). The author makes the conclusion that by the using of the traditional kind of genre (narrative) to describe the pilgrim campaign the both authors – I. S. Shmelev and V. N. Krupin attempt to rich the aim to do the narrative closer as much as possible to the travel notes. Also by the examination of the genre – the narrative (by B. K. Zaytsev) and short story (by V. N. Krupin) it was found that the authors often used the structure elements of canonical hagiography. So, it may be assumed that in the creative work of representatives of Russian-language literature abroad during the first wave of emigration and of V. N. Krupin as well the traditional literary genres of narrative, short story obtain the specific marks ofthe travel notes and hagiographies, thereby they underline the main ideas and disclose orthodox themes.
Keywords: nativism trend; Orthodoxy; literary genre; narrative; travel notes; short story; hagiography; idea; style; pilgrimage prose